A Review of the Application of Additive Manufacturing in Prosthetic and Orthotic Clinics from a Biomechanical Perspective. (November 2020) - Wang, Yan; Tan, Qitao; Pu, Fang; Boone, David; Zhang, Ming
Abstract: Prostheses and orthoses are common assistive devices to meet the biomechanical needs of people with physical disabilities. The traditional fabrication approach for prostheses or orthoses is a material-wasting, time-consuming, and labor-intensive process. Additive manufacturing (AM) technology has advantages that can solve these problems. Many trials have been conducted in fabricating prostheses and orthoses. However, there is still a gap between the hype and the expected realities of AM in prosthetic and orthotic clinics. One of the key challenges is the lack of a systematic framework of integrated technologies with the AM procedure; another challenge is the need to design a prosthetic or orthotic product that can meet the requirements of both comfort and function. This study reviews the current state of application of AM technologies in prosthesis and orthosis fabrication, and discusses optimal design using computational methods and biomechanical evaluations of product performance. A systematic framework of the AM procedure is proposed, which covers the scanning of affected body parts through to the final designed adaptable product. A cycle of optimal design and biomechanical evaluation of products using finite-element analysis is included in the framework. A mature framework of the AM procedure and sufficient evidence that the resulting products show satisfactory biomechanical performance will promote the application of AM in prosthetic and orthotic clinics.